Navigating Market Paradoxes: A Philosophical Reconstruction of MSME Marketing Strategy in the Era of Digital Transformation - Ardhi Setyo Putranto (Ridwan Institute, 2026)
The marketing strategy development process can be characterized as nonlinear, iterative, and responsive to new technologies, market opportunities, and evolving social ethics. This article aims to contribute to the investigation of the application of dialectical philosophy to the evolution of marketing practices, particularly concerning micro and small enterprises (MSEs). This article is the result of an exploratory literature review and thematic analysis of scientific communication published between 2020 and 2026. The marketing practices of MSEs are subject to paradoxical, and especially dualistic, factors, including tensions between resource constraints and technology adoption, data-based personalization versus individual privacy, and the ethics of disruptive digital business innovation. From a dialectical perspective, these dualisms are not merely obstacles; rather, they can be viewed more positively as focal points that enable organizations to adjust, grow, and improve strategies under resource limitations. An integrated dialectical marketing philosophy provides a framework for MSEs that captures this iterative process and, above all, aims to achieve an ethically, contextually, and constructively evolving sustainable paradigm—the Positively Change Framework. When small and micro enterprises (SMEs) develop marketing strategies, they should give careful consideration to both ethics and context.